2014
DOI: 10.3402/dfa.v5.24926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of painless diabetic neuropathy on pressure pain hypersensitivity (hyperalgesia) after acute foot trauma

Abstract: Introduction and objectiveAcute injury transiently lowers local mechanical pain thresholds at a limb. To elucidate the impact of painless (diabetic) neuropathy on this post-traumatic hyperalgesia, pressure pain perception thresholds after a skeletal foot trauma were studied in consecutive persons without and with neuropathy (i.e. history of foot ulcer or Charcot arthropathy).Design and methodsA case–control study was done on 25 unselected clinical routine patients with acute unilateral foot trauma (cases: elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In a study by Wienemann et al ., they concluded that physiological nociception and posttraumatic hyperalgesia to pressure is diminished at the foot with severe painless (diabetic) neuropathy. [ 16 ] This suggests that patients with painless diabetic neuropathy experience less posttraumatic/postsurgical pain in comparison to patients with painful diabetic neuropathy. This may be due to diabetic nerve damage leading to less pain.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Wienemann et al ., they concluded that physiological nociception and posttraumatic hyperalgesia to pressure is diminished at the foot with severe painless (diabetic) neuropathy. [ 16 ] This suggests that patients with painless diabetic neuropathy experience less posttraumatic/postsurgical pain in comparison to patients with painful diabetic neuropathy. This may be due to diabetic nerve damage leading to less pain.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine blockade of cutaneous nociceptors, increasing mechanical pain thresholds, but not tactile detection thresholds ( 32 ), changes the character of mechanically stimulated pain from sharp pricking pain to dull pressure discomfort ( 15 ). Interestingly, the mechanoreceptors stimulated by conventional algometer are subject to sensitisation from inflammation due to a single strong trauma ( 4 ), or chronic repetitive submaximal trauma ( 33 , 34 ), since DPPPT and mechanical detection threshold decrease in response to these conditions in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The following structures were co-stimulated: glabrous skin and subdermal fat tissue, plantar fascia; medial plantar vein artery and nerve. Previous studies had reported that healthy subjects’ 1 cm 2 DPPPT averages around 20 to 50 N/cm 2 over abductor hallucis muscle ( 1 , 4 , 5 , 27 , 28 ).…”
Section: Methodsmentioning
confidence: 96%
“…27 At the palmar side of the hand, the average pinprick-pain perception threshold is around 250 mN, and at the plantar side of the foot, it is around 120 mN. 28,29 Due to acquired individual psycho-physical irritability, 30 the pain response to pinprick stimulation varies little intraindividually, but considerably between people. Hence, in healthy human populations, the range of pinprick-pain perception thresholds is wide, reaching from <10 mN (1 g) to >1000 mN (100 g), with a bell-shaped logarithmic distribution, see Mücke et al 17…”
Section: Methodsmentioning
confidence: 99%